2022
DOI: 10.3389/fmed.2022.896811
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Kallikrein Generation in Women With Preeclampsia: A Matched Cross-Sectional Study

Abstract: ObjectiveThe pathophysiology of preeclampsia is not fully understood. Disturbances in the contact system are associated with preeclampsia. Few studies have investigated the association between preeclampsia and alterations in the contact system in plasma. This study aims to elucidate whether this basic biological system is affected in preeclampsia using new methods focusing on the dynamic interactions and total capacity of the contact system in blood.DesignCross-sectional study matching women with preeclampsia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Despite the delay in thrombin formation, the thrombin-generating capacity of CAS, in terms of ETP and peak thrombin concentration, is significantly higher in women with preeclampsia than controls. We have previously demonstrated that the plasma concentration of FXII and HK are comparable in our patients with preeclampsia and controls, whereas prekallikrein is lower in the patients with preeclampsia [10]. Hence, differences in the concentration of the CAS proteins are presumably not responsible for the observed differences in thrombin generation.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Despite the delay in thrombin formation, the thrombin-generating capacity of CAS, in terms of ETP and peak thrombin concentration, is significantly higher in women with preeclampsia than controls. We have previously demonstrated that the plasma concentration of FXII and HK are comparable in our patients with preeclampsia and controls, whereas prekallikrein is lower in the patients with preeclampsia [10]. Hence, differences in the concentration of the CAS proteins are presumably not responsible for the observed differences in thrombin generation.…”
Section: Discussionmentioning
confidence: 56%
“…A prolonged lag time may in general be related to increased C1inh, the major inhibitor of CAS. But C1inh is reduced in both controls and women with preeclampsia, and the concentration of C1inh is not significantly different between the two groups [10]. These results suggest that C1inh is not responsible for the prolonged lag time observed in women with preeclampsia.…”
Section: Main Findingsmentioning
confidence: 67%
See 2 more Smart Citations
“…The patient cohort is described previously. 11 In brief, the Preeclampsia and ContAct System study (PreCAS) is a matched cross-sectional trial conducted from January 2020 to October 2021. Patients were included at Departments of Obstetrics and Gynecology at University Hospital of Southern Denmark, Esbjerg and Odense.…”
Section: Methodsmentioning
confidence: 99%